La valeur juridique du projet de loi reconnaissant l'égalité des deux communautés linguistiques officielles au Nouveau-Brunswick - Bastarache, Michel (Les Cahiers de droit, 1981)
The principles that an Act Recognizing the Equality of the Two Official Linguistic Communities in New Brunswick would incorporate in the laws would be better put in the preamble to a constitution, because of their symbolic and educational value. They comprise two possible fundamental protections : the first is protection against discrimination (or the entrenchment of formal equality) ; the second is protection against assimilation (or resultant equality). It is this second objective which stresses the need for the recognition of collective rights in New Brunswick, such as the right to distinct social, educational and cultural institutions and, by implication, the need for the most advanced form of autonomy possible for each distinct linguistic community. One may wonder whether the Act gives the courts of New Brunswick a clear enough indication of the objectives of the Legislature to allow them to put aside the restrictive concept of equality developed in the interpretation of human rights legislation in Canada ? It would seem that the preamble to the Act limits its purpose to a declaration of principle. This legislative intent is best demonstrated by the fact that no section giving a right of action to citizens is included. The Act also has some very important limitations that result from various difficulties of interpretation. These difficulties are enhanced by the fact that the Act itself is not constitutional in nature. Section 1 borrows its language from Section 2 of the Official Languages Act of Canada, this section having been interpreted in a positive but uncertain way in Air Canada v. Joyal. Given the fact that the purpose of the Act, as set out in the preamble, is to create a set of political principles for the government of New Brunswick, it is difficult to see where it could be given a wider interpretation than the Canadian Bill of Rights with regard to the term « equality ». Whatever success was obtained in the courts has depended on the fact that the rights set out were in each instance very clear. Section 2 is the most difficult to understand because it gives no indication as to the means through which the government of New Brunswick is to ensure equality between the linguistic communities. The reference to distinct institutions is extremely uncertain and could only be given some legal force if the courts were to recognize that they have the duty to determine the true meaning of the section in a discretionary manner. But here the Act does not provide for any sanction and reflects the intention of creating declaratory legislation only. Section 3 is more or less a declaration of intent. The problem raised by the adoption of Acts of a declaratory nature was raised last year in the Forest case. The difficulty is that the declaratory judgment does not generally constitute an order given to the government or the Legislature to act in a specific way. In the United States, the Courts of Equity found that they could take into consideration the common interest in deciding whether there were obstacles to a mandatory order resulting from the application of declaratory legislation. In Canada, the courts have been very timid. One might ask whether the Act is likely to bring about a better understanding between the two linguistic communities of New Brunswick. Politically, it is obvious that the Act will not provide a true framework for political change. Legally, it can be said without doubt that the Act will not create any rights or bring about an era of judicial interventionism. However, even an implicit adoption of the concept of collective rights could mark a turning point in the relationship between the two linguistic communities in New Brunswick.